2012
DOI: 10.17221/6272-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of ejaculate quality and selected biochemical parameters of blood in cockerels of three laying lines

Abstract: In domestic fowl (Gallus gallus f. domestica), monitoring of both quantitative and qualitative parameters of ejaculates is an indispensable precondition of successful artificial insemination; on the basis of the obtained results it is then possible to select the individuals that produce sufficient amounts AbstRAct: Ejaculates and blood plasma were sampled from cocks of three laying lines: Barred Plymouth Rock (BPR), Sussex Light (SU), and Rhode Island Red (RIR). Ejaculates and blood plasma were sampled four ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
0
1
Order By: Relevance
“…Mean concentration of spermatozoa was significantly (P>0.05) higher in RIR X Local Cross (2.80±11.4 × 10 9 /ml) as compared to Punjab Red and RIR (2.13 ± 8.12, 1.83 ± 7.76 × 10 9 /ml). A higher sperm concentration (4.8 x 10 9 /ml) was observed in RIR reported by Jarinkovicova et al 2008 in comparison to our observations. On the contrary low sperm concentration of 0.75 x 10 9 /ml (Bah et al, 2001), 1.47 x 10 9 /ml (Shanmugam et al, 2013) and 1.59 x 10 9 (Denisa et al, 2015) have been reported in RIR.…”
Section: Resultscontrasting
confidence: 67%
“…Mean concentration of spermatozoa was significantly (P>0.05) higher in RIR X Local Cross (2.80±11.4 × 10 9 /ml) as compared to Punjab Red and RIR (2.13 ± 8.12, 1.83 ± 7.76 × 10 9 /ml). A higher sperm concentration (4.8 x 10 9 /ml) was observed in RIR reported by Jarinkovicova et al 2008 in comparison to our observations. On the contrary low sperm concentration of 0.75 x 10 9 /ml (Bah et al, 2001), 1.47 x 10 9 /ml (Shanmugam et al, 2013) and 1.59 x 10 9 (Denisa et al, 2015) have been reported in RIR.…”
Section: Resultscontrasting
confidence: 67%